2012
DOI: 10.1186/1475-2891-11-89
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the yellow passion fruit peel flour (Passiflora edulis f. flavicarpa deg.) in insulin sensitivity in type 2 diabetes mellitus patients

Abstract: BackgroundA study with the yellow passion fruit peel flour showed positive action in blood glucose control as therapies’ adjuvant in patients with type 2 diabetes mellitus. Therefore, we evaluated its effect on insulin sensitivity since there is a quest for studies that focus at better understanding of insulin resistance aspects in diabetic patients. Furthermore its relationship with chronic complications can also give good prospects for alternative treatments.MethodsA total of 43 type 2 diabetes volunteers (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
0
19
0
10
Order By: Relevance
“…Estudos têm demonstrado que o consumo da casca do maracujá pode ajudar no tratamento coadjuvante do controle glicêmico, com diminuição signifi cativa na glicemia de jejum, hemoglobina glicada, índice HOMA IR e aumento no índice HOMA (QUEIROZ et al, 2012); assim como no controle lipêmico, promovendo redução do colesterol total e fração LDL (RAMOS et al, 2007). Além disso, estudo com modelo experimental demonstrou efeito anti-infl amatório, com diminuição do volume do edema, liberação de mieloperoxidase, infi ltração de neutrófi los e da expressão de TNF- e iNOS (SILVA et al, 2011).…”
Section: Resultsunclassified
“…Estudos têm demonstrado que o consumo da casca do maracujá pode ajudar no tratamento coadjuvante do controle glicêmico, com diminuição signifi cativa na glicemia de jejum, hemoglobina glicada, índice HOMA IR e aumento no índice HOMA (QUEIROZ et al, 2012); assim como no controle lipêmico, promovendo redução do colesterol total e fração LDL (RAMOS et al, 2007). Além disso, estudo com modelo experimental demonstrou efeito anti-infl amatório, com diminuição do volume do edema, liberação de mieloperoxidase, infi ltração de neutrófi los e da expressão de TNF- e iNOS (SILVA et al, 2011).…”
Section: Resultsunclassified
“…However, among these studies, only one adopted HbA1 C as an outcome, and all were based in self-controlled samples (studies of the ‘before and after’ type) [17, 18, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the presence of a high concentration of soluble fibers, especially pectin, phenolic compounds, such as isoorientin, coumarin, cyanidin-3-the-glycoside, quercetin-3-O-glycoside and edulic acid, among other yellow flavonoids. The treatment of experimental models and humans with the flour or yellow passion fruit peel extract revealed antihypertensive, antioxidant and antihyperglycaemic effects, in addition to decreased insulin resistance and hypolipidemic activity (56,57,58,59,60,61) .…”
Section: Peels: Does Their Use Bring Benefits?mentioning
confidence: 99%